Postural Sway Parameters and Gait Symmetry in Preschool Children: Cross-sectional study - Fabiane E de Sá; Renata VB de M Jucá; Abimaele B Fernandes; Fernando VA de Oliveira; Lêda M da CP Frota; Kátia V Viana-Cardoso
Abstract The most important function of posture is to ensure the maintenance of control during the start and the continuation of human movement, moreover, posture serves as a reference for the production of precise movements. The aim of this study was to relate the postural sway parameters and gait symmetry in preschool children.This study is a cross-sectional study, conducted in 49 children with a mean age of 4.65 ± 0.44 years. Initially, height and body mass of children were measured using anthropometric scales. Next, an electronic baropodometer was used to evaluate the distribution of dynamic plantar pressure (gait) and stabilometry (balance).A Student t test or Mann-Whitney test for comparing two groups was used. To correlate variables, a Pearson's correlation or Spearman's correlation coefficient was used. The stabilometric parameters showed no significant difference between an eyes open test and eyes closed test in preschool child. We found a moderate relationship between axis inclination and cadence symmetry (R=0.40;p=0.007). Postural sway parameters have relationship cadence symmetry of the gait in preschool children.